2015
DOI: 10.1080/15476286.2015.1014759
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 RRE RNA acts as an RNA silencing suppressor by competing with TRBP-bound siRNAs

Abstract: Several proteins and RNAs expressed by mammalian viruses have been reported to interfere with RNA interference (RNAi) activity. We investigated the ability of the HIV-1-encoded RNA elements Trans-Activation Response (TAR) and RevResponse Element (RRE) to alter RNAi. MicroRNA let7-based assays showed that RRE is a potent suppressor of RNAi activity, while TAR displayed moderate RNAi suppression. We demonstrate that RRE binds to TAR-RNA Binding Protein (TRBP), an essential component of the RNA Induced Silencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 87 publications
(139 reference statements)
1
19
0
Order By: Relevance
“…To determine if PACT can enhance HIV-1 long terminal repeat (LTR)-driven gene expression in the context of latently infected cells, we first compared the effects of TRBP and PACT when HIV-1 LTR is integrated into the host chromosome. HeLa-MAGI-CCR5 cells contain a stably integrated β-galactosidase-coding region expressed under the control of the HIV-1 LTR, whose transcription is dependent on HIV-1 Tat protein [45][46][47][48][49]. We first verified that increasing amounts of Tat expression vector (blue bars) resulted in a dose-dependent increase in β-galactosidase activity ( Figure 1A) compared with the absence of Tat (black bar).…”
Section: Pact Enhances Hiv-1 Gene Expression From a Tat-induced Integmentioning
confidence: 86%
“…To determine if PACT can enhance HIV-1 long terminal repeat (LTR)-driven gene expression in the context of latently infected cells, we first compared the effects of TRBP and PACT when HIV-1 LTR is integrated into the host chromosome. HeLa-MAGI-CCR5 cells contain a stably integrated β-galactosidase-coding region expressed under the control of the HIV-1 LTR, whose transcription is dependent on HIV-1 Tat protein [45][46][47][48][49]. We first verified that increasing amounts of Tat expression vector (blue bars) resulted in a dose-dependent increase in β-galactosidase activity ( Figure 1A) compared with the absence of Tat (black bar).…”
Section: Pact Enhances Hiv-1 Gene Expression From a Tat-induced Integmentioning
confidence: 86%
“…Therefore, it is possible that Tat binds to specific precursor miRNAs in a sequence-dependent manner, inhibiting Dicer processing of this subset of miRNAs. Additionally, a structured RNA element of the HIV-1 genome, the Rev-response element (RRE), binds to the TRBP, a central component of the Dicer complex [ 176 , 177 , 178 ]. This interaction further inhibits the RNA silencing pathway by competing with TRBP-bound RNAs [ 177 ].…”
Section: Retrovirusesmentioning
confidence: 99%
“…Additionally, a structured RNA element of the HIV-1 genome, the Rev-response element (RRE), binds to the TRBP, a central component of the Dicer complex [ 176 , 177 , 178 ]. This interaction further inhibits the RNA silencing pathway by competing with TRBP-bound RNAs [ 177 ]. Similarly to HIV-1, the primate foamy virus type 1 (PFV-1) encoded transactivator (Tas) also interferes with miRNA processing, and might function to overcome suppression of PFV-1 replication mediated by the cellular miRNA, miR-32 [ 179 ].…”
Section: Retrovirusesmentioning
confidence: 99%
“…The active strand of such mature miRNA is retained in the Dicer-TRBP complex, which then binds with the endonuclease AGO2. One strand of the mature miRNA (the guide strand) is loaded into the RISC target mRNAs that are complementary to the miRNA [84]. Huang et al [85] revealed that TRBP is overexpressed in BC.…”
Section: Trbpmentioning
confidence: 99%